Environmental Shocks: Modelling the Dynamics. (August 2018) - Didenko, N I; Kulik, S V
Abstract: This paper reports on processes occurring within the human environment: shocks occurring in the environment; the increase in greenhouse gases from industry; the increase in greenhouse gases from agriculture; the change in global temperature; the reduction of freshwater resources; the change in area of forested land. The article also examines the impact of three groups of factors on the dynamics of environmental shocks. These factors are the history of the process, the impact of various dynamic factors of human life and the degree of influence of the processes occurring in the environment. The autoregressive distributed lags model (ADL model) is chosen as the theoretical framework for the analysis of the correlation between the environmental shocks and the influencing factors, and empirical testing of the model is performed. The exogenous variables characterising the factors of human life were analysed using the following indices: global GDP per capita; economically active global population; global merchandise exports (FOB); rail transport freight turnover (mln tons km -1 ); the mining of coal and lignite, extraction of peat, (mln USD). The forecast of the development of environmental shocks in 2017-2018 was performed. The analysis of the model showed that the dynamics of the environmental shocks had a constant trend.